THE IMPACT OF THE RUSSIAN EMPIRE’S CONQUEST ON THE ECONOMY OF THE KOKAND AND KHIVA KHANATES AND THE EMIRATE OF BUKHARA (Eureka Journal of Humanities and Social Research, 2026)
This article examines the abolition of the Emirate of Bukhara and the Khanates of Kokand and Khiva, as well as the treaties concluded between the Russian Empire and the Turkestan khanates. Particular attention is paid to the colonial nature embedded in these agreements, their legal consequences, and their influence on the economic life of the region.
Keywords: Contract, commerce, land tax, customs duty, law, indemnity, ruble, Amu Darya department.